Assessing User Experience of the Online Petition System in Indonesia based on UEQ - Ika Nurlaili Isnainiyah; Bambang Triwahyono (STMIK Budi Darma, 2021)
This study analyzes the user experience of online petition system Petisionline.com towards the participatory culture of Indonesian citizens. This participation can be in the form of citizens’ individual opinions to involvement in communities or groups. The user experience analysis in this study refers to the assessment using modified long version of User Experience Questionnaire (UEQ) which consists of six experiences scales, namely attractiveness, perspicuity, efficiency, dependability, stimulation and novelty. Based on the scoring results of 26 items from UEQ, dependability and novelty scale scored the lowest among other scales. Petisionline.com needs to improve the aspects related to both scales to enhance its role in facilitating the participatory culture.